Time-Resolved Fluorescence Anisotropy of Bicyclo[1.1.1]pentane/Tolane-Based Molecular Rods Included in Tris(o-phenylenedioxy)cyclotriphosphazene (TPP) - Cipolloni, Marco; Kaleta, Jiří; Mašát, Milan; Dron, Paul I; Shen, Yongqiang; Zhao, Ke; Rogers, Charles T; Shoemaker, Richard K; Michl, Josef (The journal of physical chemistry. C, Nanomaterials and interfaces, 2015)
We examine the fluorescence anisotropy of rod-shaped guests held inside the channels of tris(o-phenylenedioxy)cyclotriphosphazene (TPP) host nanocrystals, characterized by powder X-ray diffraction and solid state NMR spectroscopy. We address two issues: (i) are light polarization measurements on an aqueous colloidal solution of TPP nanocrystals meaningful, or is depolarization by scattering excessive? (ii) Can measurements of the rotational mobility of the included guests be performed at low enough loading levels to suppress depolarization by intercrystallite energy transfer? We find that meaningful measurements are possible and demonstrate that the long axis of molecular rods included in TPP channels performs negligible vibrational motion.